Petrogenesis of ore-forming and pre/post-ore granitoids from the Kounrad, Borly and Sayak porphyry/skarn Cu deposits, Central Kazakhstan - Li, G.; Cao, M.; Qin, K.; Hollings, P.; Evans, Noreen; Seitmuratova, E. (2015)
Ore-forming porphyries and barren granitoids from porphyry Cu deposits differ in many ways, particularly with respect to their adakitic affinity and calc-alkaline characteristics. In this study, zircon U–Pb and molybdenite Re–Os dating, whole rock geochemistry, whole rock Sr–Nd–Pb and zircon O–Hf isotopic analyses were carried out on the ore-forming granitoids from the Kounrad, Borly and Sayak deposits, and also on pre-ore and post-ore granitoids in adjacent regions of Central Kazakhstan. Geochronology results indicate that pre-ore magmatism occurred in the Late Devonian to Early Carboniferous (361.3–339.4 Ma), followed by large scale Cu mineralization (325.0–327.3 Ma at Kounrad, 311.4–315.2 Ma at Borly and 309.5–311.4 Ma at Sayak), and finally, emplacement of the Late Carboniferous post-ore barren granitoids (305.0 Ma). The geochemistry of these rocks is consistent with calc-alkaline arc magmatism characterized by strong depletions in Nb, Ta and Ti and enrichments in light rare earth elements and large ion lithophile elements, suggesting a supra-subduction zone setting. However, the ore-forming rocks at Kounrad and Sayak show adakitic characteristics with high Sr (517.5–785.3 ppm), Sr/Y (50.60–79.26), (La/Yb)N (9.37–19.62) but low Y (6.94–11.54 ppm) and Yb (0.57–1.07 ppm), whereas ore-forming rocks at Borly and barren rocks from northwest of Borly and Sayak have normal arc magma geochemical features. The Sr–Nd–Hf–O isotopic compositions show three different signatures: (1) Sayak granitoids have very young juvenile lower crust-derived compositions ((87Sr/86Sr)i = 0.70384 to 0.70451, ɛNd (t) = + 4.9 to + 6.0; TDM2 (Nd) = 580 to 670 Ma, ɛHf (t) = + 11.3 to + 15.5; TDMC (Hf) = 330 to 600 Ma, δ18O = 6.0 to 8.1‰), and were probably generated from depleted mantle-derived magma with 5–15% sediment melt addition in the magma source; (2) the Kt-1 granite from northwest of Sayak shows extremely enriched Sr–Nd isotopic compositions ((87Sr/86Sr)i = 0.71050, ɛNd (t) = − 7.8, TDM2 (Nd) = 1700 Ma), likely derived from partial melting of ancient continental crust; (3) other granitoids have transitional Sr–Nd compositions between the Sayak and Kt-1 samples, indicating a juvenile lower crust source with the addition of 10–30% of ancient crustal material. The pre-ore magmatism was probably related to partial melting of juvenile lower crust due to northward subduction of the Junggar–Balkhash Ocean, whereas the ore-forming adakitic rocks at Aktogai, Kounrad and Sayak formed by partial melting of thickened lower crust which subsequently delaminated. The ore-forming rocks at Borly, and the later post-ore barren granites, formed by partial melting of juvenile lower crust with normal thickness. This tectonic setting supports the existence of an Andean-type magmatic arc in the Devonian to the Late Carboniferous, resulting from the subduction of the Junggar–Balkhash oceanic plate. The link between whole rock geochemistry and scale of mineralization suggests a higher metallogenic potential for adakitic rocks than for normal arc magmatism.